The effects of self-perceived aging and emotion regulation strategies on psychological abuse of elderly people in rural China: a structural equation modeling approach - Pei, Li; Zhao, Dongqing; Cao, Futing; Li, Shuang; Zhang, Lanrui; Wu, Xiaomeng; Pang, Xiaoli; Dou, Haoying (Frontiers in Psychology, 2025)
BackgroundIn China, psychological abuse is increasingly prevalent among elderly people. Psychological abuse can have a significant negative impact on elderly people in terms of worsening chronic illness, increased suicide rick and death. Previous studies have suggested that self-perceived aging may serve as a risk factor for psychological abuse. However, the immediate impact of self-perceived aging on psychological abuse within Chinese culture remains unclear.ObjectivesThis study aimed to investigate the relationship between self-perceived aging and psychological abuse among rural Chinese older adults, while considering the parallel mediating role of emotion regulation strategies (including cognitive reappraisal and expressive inhibition).Research design and methodsA cross-sectional design was used in this study. A total of 449 rural older adults were recruited from a county in Dezhou City, Shandong Province, from July to October 2023 to assess self-perceived aging, cognitive reappraisal, expressive inhibition and psychological abuse. A hypothesized model based on Socioemotional Selectivity Theory pathways was proposed to examine the relationships between self-perceived aging, cognitive reappraisal, expressive inhibition and psychological abuse.ResultsHigher self-perceived aging and expressive inhibition were positively associated with the propensity to be psychological abuse, and cognitive reappraisal was negatively associated with psychological abuse. Structural equation modeling revealed that the cognitive reappraisal and expressive inhibition strategy mediated the relationship between self-perceived aging and psychological abuse.Discussion and implicationsThis study reveals that self-perceived aging is associated with the occurrence of psychological abuse in older adults as they enter the aging stage. It further suggests that part of this effect can be explained by cognitive reappraisal or expressive inhibition. Thus, the use of emotion regulation strategies may help to reduce the incidence of psychological abuse after self-perceived aging.